Efficacy and safety of serplulimab plus nab-paclitaxel in previously treated patients with PD-L1–positive advanced cervical cancer: a phase II, single-arm study - An, Jusheng; Li, Xiumin; Wang, Jing; Zhu, Lijing; An, Ruifang; Jiang, Kui; Huang, Yi; Wang, Ke; Li, Guiling; Wang, Chunyan; Yuan, Jianlin; Hou, Xiaoli; et al. (Frontiers in Immunology, 2023)
Objective: We report the efficacy and safety of serplulimab, a novel humanized anti–programmed death-1 antibody, plus nanoparticle albumin-bound (nab)-paclitaxel in previously treated patients with programmed death ligand-1 (PD-L1)–positive advanced cervical cancer. Methods: Patients diagnosed with PD-L1–positive (combined positive score ≥1) cervical cancer were enrolled in this single-arm, open-label, phase II study. They were given serplulimab 4.5 mg/kg for up to 2 years (35 dosing cycles) plus nab-paclitaxel 260 mg/m2 for up to six cycles once every 3 weeks. Primary endpoints were safety and objective response rate (ORR) assessed by independent radiological review committee (IRRC) per RECIST version 1.1. Secondary endpoints included ORR assessed by the investigator, duration of response (DOR), progression-free survival (PFS), and overall survival (OS). Results: Between December 2019 and June 2020, 52 patients were screened and 21 were enrolled. IRRC-assessed ORR was 57.1% (95% confidence interval [CI] 34.0–78.2%); 3 (14.3%) patients achieved complete response and 9 (42.9%) partial response. The median DOR was not reached (NR) (95% CI 4.1–NR). IRRC-assessed median PFS was 5.7 months (95% CI 3.0–NR), and median OS was 15.5 months (95% CI 10.5–NR). Investigator-assessed ORR was 47.6% (95% CI 25.7–70.2%). Seventeen (81.0%) patients experienced grade ≥3 treatment-emergent adverse events. Grade ≥3 adverse drug reactions were reported in 7 (33.3%) patients. Immune-related adverse events occurred in 12 (57.1%) patients. Conclusions: In previously treated patients with PD-L1–positive advanced cervical cancer, serplulimab plus nab-paclitaxel provided durable clinical activity and a manageable safety profile. Clinical Trial Registration: https://ClinicalTrials.gov, identifier NCT04150575